Patenteamento segundo a origem no crescimento econômico : evidências para a indústria de transformação brasileira - Duarte, Jordana Teatini (2018)
The purpose of the patent system is to boost technological progress by giving the inventor the legal exploration of his innovation. Thus, patents represent a minimal quantum of technology, which has been scrutinized by a thorough research of the industrial property office. In this context, the present study aims to analyze the patenting activity in Brazil between 2000 and 2012. Specifically, it is sought to observe the Brazilian System of Innovation from patent statistics and, later, verify if patents from residents and non residents deposited on the National Institute of Industrial Property – INPI – have an impact on the sectors’ productivity of the Brazilian Manufacturing Industry. These sectors were constructed based on a conversion between the technological fields of patents and the methodologies of National Classification of Economics’ Activity (CNAE) 1.0 and 2.0. As an econometric strategy, the Feasible Generalized Least Squares (FGLS) method was used, with data taken from the Annual Industrial Survey (PIA) and the Industrial Property Statistical Database (BADEPI). The main results show that there is a pattern of regional and sectoral concentration of the national technological activity, which is derived from the mismatch between the agents and policies that compose the national innovation system, which did not align the sectors and regions of the country in favor of economic and technological development. With regard to the impact of patents according to their origins on industrial production, it was clear that, in the face of a cultural and institutional issue, the patenting system is not opportune and does not fulfill its objective of promoting the efficient use of industrial property. This outcome signals the deficiency of Brazil in carrying out the catching up process towards more developed economies.